Development of a 1-D salt intrusion modelling programme using python programming language - Loh, Ri Jian (2017)
Salt intrusion model mostly does not standalone and is integrated into 2-D and 3-D hydraulics modelling tools such as Mike21 and Delft-3D. Although the integration looks convenient, the models are very expensive due to its costly license procurement. As an alternative, 1-D salt intrusion model generates a simpler and economical platform for the user to conduct study on salt intrusion in estuaries. The objective of this study are 1) to develop a 1-D analytical salt intrusion modelling programme using Python programming language: SALT 2) to simulate the longitudinal salinity curve using developed programme and 3) to validate the applicability and reliability of the model. In this study, the SALT modelling programme has been developed using Python programming language to protect the formulas that can be easily changed in traditional spreadsheet. The core concept of this model adopts the analytical 1-D salt intrusion model developed by Savenije (2005) and Gisen (2015).The existing salt intrusion data of Malaysia estuaries were divided into two sets, one for model validation (Kurau, Perak, Bernam, Selangor, Muar and Endau) from Gisen (2015) and another set for model testing on the newly surveyed Belat Estuary. Based on the comparison between the result obtained from the conventional spreadsheet and SALT, the SALT modelling programme is indeed reliable to be used for salt intrusion study application as the model performance analyses show high accuracy with average RMSE of 1.31 and average NSE of 0.98.